Seismic performance assessment of deficient RC structures retrofitted with different steel bracing systems - Meriem Bouderradji; Mohammed Salah Dimia; Soumia Gherabli; Ahmed Rafik Belakhdar; Noureddine Lahbari (The Journal of Engineering and Exact Sciences)
This paper discusses the use of concentric steel bracing systems as a global technique for retrofitting RC structures. A case study building with a five-story RC structure was retrofitted and tested using different types of bracing systems with different arrangements namely diagonal, X, and a combination between diagonal and X steel braces with tow arrangements. The main objective of the current study is to find out the most effective bracing system to upgrading the seismic behavior of deficient RC structures. The nonlinear static pushover and dynamic time-history analyses were carried out. The first method was applied by pushing the models until they arriving at a predefined target roof displacement. In the second method, a set of three natural earthquakes was employed to perform a dynamic time history analysis. The results indicate that the combined system of the diagonal and X braces using the second arrangement has the highest base shear and reaches the target roof displacement under pushover analysis. On the other hand, when using the response history analysis, it is the best system to reduce roof displacement compared to other techniques. However, steel braces cannot reduce the acceleration of the structure. The proposed combined system with the second arrangement is an effective retrofitting technique that has a much better seismic behavior and improves the ability to withstand even larger earthquake forces compared to other techniques.